The functionality of the family in building the resilience of narcotics abusers undergoing rehabilitation - Annisya, Sri (Institute for Advanced Science, Social, and Sustainable Future, 2025)
Background: Drug abuse remains a serious global and national issue, with South Sumatra among the provinces with the highest prevalence in Indonesia. Rehabilitation efforts often face challenges such as relapse, which is influenced by internal and external factors, particularly family support and functioning. This study aims to examine the role of family functioning in strengthening the individual resilience of narcotics abusers undergoing rehabilitation in South Sumatra Province. Methods: This study employed a quantitative causal design using a survey method and Structural Equation Modeling (SEM) to analyze the influence of family functioning on individual resilience among 106 narcotics abusers undergoing rehabilitation in South Sumatra. Findings: The findings reveal that family functionality significantly affects individual resilience (path coefficient = 0.60; t = 5.20), indicating that emotional support, parental involvement, and effective communication play a critical role in preventing relapse during rehabilitation. Conclusion: The research shows that family functionality plays a vital role in fostering resilience among narcotics abusers by providing emotional support, open communication, and guidance throughout the rehabilitation process. Active family involvement, especially in supervision and positive engagement, significantly aids in preventing relapse and sustaining recovery. Novelty/Originality of this article: The novelty/originality of this article lies in quantitatively analyzing how specific aspects of family functioning significantly enhance individual resilience and reduce relapse risk among narcotics abusers undergoing rehabilitation in South Sumatra.